Histone H4K20 methylation mediated chromatin compaction threshold ensures genome integrity by limiting DNA replication licensing - Shoaib, Muhammad; Walter, David; Gillespie, Peter J.; Izard, Fanny; Fahrenkrog, Birthe; Lleres, David; Lerdrup, Mads; Johansen, Jens Vilstrup; Hansen, Klaus; Julien, Eric; Blow, J. Julian; Sørensen, Claus S. (Nature communications, 2018)
The decompaction and re-establishment of chromatin organization immediately after mitosis is essential for genome regulation. Mechanisms underlying chromatin structure control in daughter cells are not fully understood. Here we show that a chromatin compaction threshold in cells exiting mitosis ensures genome integrity by limiting replication licensing in G1 phase. Upon mitotic exit, chromatin relaxation is controlled by SET8-dependent methylation of histone H4 on lysine 20. In the absence of either SET8 or H4K20 residue, substantial genome-wide chromatin decompaction occurs allowing excessive loading of the origin recognition complex (ORC) in the daughter cells. ORC overloading stimulates aberrant recruitment of the MCM2-7 complex that promotes single-stranded DNA formation and DNA damage. Restoring chromatin compaction restrains excess replication licensing and loss of genome integrity. Our findings identify a cell cycle-specific mechanism whereby fine-tuned chromatin relaxation suppresses excessive detrimental replication licensing and maintains genome integrity at the cellular transition from mitosis to G1 phase. Cell cycle and replication need to be tightly regulated to ensure genome stability in mammalian cells. Here the authors provide a link between chromatin structure and DNA replication regulation by showing that chromatin compaction limits replication licensing thereby promoting genome integrity.